P230 Symptomatic benefit of olodaterol QD delivered via Respimat® vs placebo and formoterol BID in patients with COPD: combined analysis from two 48-week studies. (14th November 2013) - Koch, A; Paggiaro, P; Hamilton, A; Hart, L; Korducki, L; De Salvo, Mc; Pizzichini, E
Abstract : Background: The novel LABA olodaterol has 24-h bronchodilator activity. Objective: To evaluate the symptomatic benefit of olodaterol QD in patients with GOLD 2–4 COPD. Methods: In replicate, randomised, double-blind, placebo-controlled, parallel-group studies, patients with post-bronchodilator FEV1 <80% predicted normal and FEV1 /FVC <70% received olodaterol (5 or 10 µg) QD via Respimat ®, formoterol (12 μg) BID via Aerolizer ® or placebo for 48 weeks (Study A: NCT00793624 ; Study B: NCT00796653 ). Patients continued to receive usual care background COPD maintenance therapy, including SAMA, LAMA, ICS and xanthines. In addition to FEV1 -based primary end points, TDI and SGRQ after 24 weeks were identified as co-primary and key secondary symptomatic end points, respectively. Results: 904 (Study A) and 934 (Study B) patients were treated. In the primary analysis using a mixed model for repeated measures (MMRM; combined dataset), there was no significant difference in TDI focal score after 24 weeks for olodaterol or formoterol vs placebo. A post hoc analysis using pattern mixture modelling (PMM) to account for discontinued patients demonstrated statistical significance for olodaterol vs placebo. There were significant improvements in SGRQ total score with olodaterol, but not formoterol, vs placebo after 24 weeks using MMRM and PMM. Conclusions: Lung function improvements with olodaterol QD translated into symptomatic benefit in COPD patients receiving usual care background therapy.